Pengembangan Media Animasi berbasis StoryTelling untuk Meningkatkan Pemahaman Materi Proklamasi pada Siswa Kelas V - Firda Febrina Hendiyani; J Juli; Rana Gustian Nugraha (Departement of Mathematics Education, 2023)
This study aims to 1) find out the process of developing storytelling-based animated media 2) find out students' responses to the development of storytelling-based animated media 3) find out the effectiveness of using storytelling-based animated video learning media 4) find out the increase in students' understanding of the proclamation material after using animated media . The research method used is design and development (D&D) using the ADDIE model. Data was collected through observation, tests and questionnaires. The research results obtained 1) The average score of media experts was 91.4% in the 'very decent' category. 2) The average score of material experts is 82% 'very decent. 3) School validation 86% category 'very feasible'. 4) The student response was 'very positive' with an average score obtained > 80%. 5) the resulting product is effective in increasing students' understanding of the proclamation material.